The Dynamics of Islamic-Based Inclusive Education at Pesantren Tri Bhakti Al-Qudwah Metro - Uswatun Hasanah; Ida Faridatul Hasanah; Azlan Abas; Asghar Abbas (Universitas Muhammadiyah Mataram, 2026)
Inclusive education based on Islamic principles in Indonesia continues to face significant challenges, particularly within Pesantren, which hold substantial potential to become pioneers of inclusive education models. Despite the growing number of children with special needs requiring equitable access to religious education, only a limited number of Pesantren have developed structured inclusive programs. This study focuses on Pesantren Tri Bhakti Al-Qudwah Metro, the first inclusive Pesantren in Lampung. It aims to examine the dynamics of Islamic-based inclusive education. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving Pesantren leaders, 5 educators, and 5 students. Data analysis followed the Miles and Huberman model. Data validity was supported by member checking and triangulation. The findings show that the inclusive model implemented in this Pesantren is rooted in the values of rahmatan lil ‘alamin, justice, compassion, and ukhuwah Islamiyah. The Pesantren develops individualized learning strategies, integrates the Sekolah Luar Biasa (SLB) and diniyah curricula, and promotes social inclusion through shared religious activities and daily routines. These practices can enhance students' religious commitment and social interaction skills. However, challenges remain, including limited availability of trained inclusive-education teachers and insufficient adaptive learning media. This study concludes that Pesantren Tri Bhakti Al-Qudwah Metro represents a transformative Islamic-based model of inclusive education. The findings of this research have implications for enriching the academic literature on Islamic-based inclusive education in the context of Indonesia’s Pesantrens. In practice, this research is expected to serve as a guideline for other Pesantrens to develop inclusive practices aligned with Islamic values.